Demographic and Socio-Economic Profile of Online Buyers: An exploration of the characteristics and behaviors of online buyers in the e-commerce era (Journal of Advances and Scholarly Researches in Allied Education, 2017)
E-commerce is a most recent technology related with commerce and PC. Commerce is the transformation or exchange or purchasing and selling of substances (merchandise or wares) on a huge scale including transportation starting with one place then onto the next. E-commerce is to direct commerce by utilizing the IT (data technology, i.e., PC technology and E- correspondence) it is the purchasing and selling of things or merchandise or administrations online utilizing E- correspondence and advanced data handling technology. EDI or E-Data Commerce is an early type of E- commerce. Its surprising expense, utilization of exclusive measures and so on hampered the spread of E- commerce. E-commerce is a composite of advances process and commerce systems that cultivate the moment commerce of data inside between associations.